The mountain is moving Japanese women's lives - Morley, Patricia A. (New York Univ. Press, 1999)
"The Mountain Is Moving describes postwar Japanese society and the roles that women are expected to play within it. Based on interviews with hundreds of women, the book explores the many spheres of women's lives, including education, marriage and child rearing, work outside the house, caring for the elderly, political power or lack of it, and volunteerism. Patricia Morley also examines a diverse and compelling range of stories and novels by and about Japanese women, revealing both the patterns that concern sociologists and the exceptions that interest philosophers and writers." "Morley asserts that the legendary Japanese system of white-collar labor can only be maintained by the efforts of women who remain at home to take care of their husbands, their children, and their aging relatives. In recent years, however, increasing numbers of Japanese women have begun to seek change and empowerment beyond the domestic sphere."--BOOK JACKET.